Argonaute proteins: structures and their endonuclease activity - Jin, Shujuan; Zhan, Jian; Zhou, Yaoqi (Molecular biology reports, 2021)
Argonaute proteins are highly conserved and widely expressed in almost all organisms. They not only play a critical role in the biogenesis of small RNAs but also defend against invading nucleic acids via small RNA or DNA-mediated gene silencing pathways. One functional mechanism of Argonaute proteins is acting as a nucleic-acid-guided endonuclease, which can cleave targets complementary to DNA or RNA guides. The cleavage then leads to translational silencing directly or indirectly by recruiting additional silencing proteins. Here, we summarized the latest research progress in structural and biological studies of Argonaute proteins and pointed out their potential applications in the field of gene editing.